2021
DOI: 10.48550/arxiv.2109.15218
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early time behavior of spatial and momentum anisotropies in a kinetic approach to nuclear collisions

Marc Borrell,
Nicolas Borghini

Abstract: We derive a general formula for the early time dependence of a phase space distribution evolving according to the kinetic Boltzmann equation. Assuming that the early evolution of the system created in high-energy nuclear collisions can be described by kinetic theory, we calculate the scaling behaviors for the onset of various characteristics of the transverse dynamics. In particular, we show that the scaling behavior of the anisotropic flow coefficients vn at early times does not depend on the details of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 44 publications
5
12
0
Order By: Relevance
“…As argued in Ref. [28], a non-vanishing v 3 can lead to a (small) linear rise of v 3 (t) at early times, which is indeed what we observe.…”
Section: Anisotropic Flow Coefficientssupporting
confidence: 90%
See 4 more Smart Citations
“…As argued in Ref. [28], a non-vanishing v 3 can lead to a (small) linear rise of v 3 (t) at early times, which is indeed what we observe.…”
Section: Anisotropic Flow Coefficientssupporting
confidence: 90%
“…In Ref. [28] we showed that the contributions at O(σ) show up at odd orders starting from t 3 , those at O(σ 2 ) start at order t 4 and show up at even order in t, while O(σ 3 )-terms again show up in odd powers of t from order t 5 on.…”
Section: Anisotropic Flow Coefficientsmentioning
confidence: 92%
See 3 more Smart Citations